Analisis Efisiensi Transportasi Laut Dalam Pengiriman Barang dan Penumpang - Faturrahman, Rifaldi (Peneliti.net, 2024)
This research aims to analyze the efficiency of maritime transport in Indonesia, given its vital role in the national economy as the largest archipelago. The focus of the research includes identifying key challenges such as uneven port infrastructure, inefficient logistics systems, and safety issues. The research method used a qualitative descriptive approach, with data sources from relevant scientific journals. A literature review technique was applied to collect, evaluate and interpret information, and to develop a topic outlook based on previous research. This process included searching, screening, and critically appraising articles. The results said that the efficiency of marine transportation is greatly influenced by cost, time, capacity, and environmental impact. With the optimization of shipping routes and environmentally friendly technologies, as well as improvements in infrastructure and supportive policies, marine transportation in Indonesia can be more efficient and sustainable, providing long-term benefits to the economy and the welfare of society.